The Influence Of Promotion And Brand Image On Purchasing Decisions With Customer Satisfaction As An Intervening Variable (Case Study On Indihome Customers Of The Company (Pt.Telekomunikasi Indonesia, Tbk Pematang Siantar Branch) - Michael Fernando Sihombing; Efendy Pakpahan; Fenny Krisna Marpaung; Tuty Nainggolan (Jurnal of Management and Social Sciences, 2025)
PT Telekomunikasi Indonesia, Tbk is a State-Owned Enterprise (BUMN) company engaged in information and communication technology. PT Telekomunikasi Indonesia, Tbk (Telkom) which is equipped with a package (3-1) three services in one package or Tripel play with communication and data service facilities provided such as landline (voice), internet (Internet on Fiber or High Speed Internet), and interactive television services (Usee TV Cable, IP TV). This study aims to determine the effect of promotion and brand image on purchasing decisions with customer satisfaction as an intervening variable (Case Study on Indihome Company Customers (PT. Telekomunikasi Indonesia, Tbk Pematang Siantar Branch). this research is non-probability, namely convenience sampling with the population, namely all customers of PT. Telekomunikasi Indonesia, Tbk Pematang Siantar Branch and the sample used was 96 respondents. The data collection technique used is primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique uses quantitative data processed with the SPSS version 29 program, namely the t test and the coefficient of determination (R2). The results obtained in this study show, 1) there is a significant effect of promotion and brand image on customer satisfaction, 2) there is a significant effect of promotion and brand image on purchasing decisions, 3) Customer satisfaction variables have a significant effect on purchasing decisions, 4) Customer satisfaction variables are not able to mediate between promotion and brand image on purchasing decisions.